S100A8 as a Promising Biomarker and Oncogenic Immune Protein in the Tumor Microenvironment: An Integrative Pancancer Analysis. (18th March 2022) - Wu, Zixuan; Jiang, Dongli; Huang, Xuyan; Cai, Minjie; Yuan, Kai; Huang, Peidong
Abstract : Background . S100 Calcium Binding Protein A8 (S100A8) is beneficial for cancer immunotherapy. However, the processes underlying its therapeutic potential have not been completely studied. Methods . The Cancer Genome Atlas provides raw data on 33 different cancer types. GEO made available GSE67501, GSE78220, and IMvigor210. We investigated S100A8's genetic changes, expression patterns, and survival studies. The linkages between S100A8 and TME, as well as its association with immunological processes/elements and the major histocompatibility complex, were explored to effectively understand the role of S100A8 in cancer immunotherapy. Three distinct immunotherapeutic cohorts were employed to examine the relationship between S100A8 and immunotherapeutic response. Results . S100A8 expression was high in tumor tissue. The overexpression of S100A8 is associated with poor clinical outcome in patients with overall survival. S100A8 is associated with immune cell infiltration, immunological modulators, and immunotherapeutic indicators. S100A8 overexpression is connected to immune-related pathways. However, no statistically significant connection between S100A8 and immunotherapeutic response was identified. Conclusions. S100A8 may be a reliable biomarker for tumor prognosis and a viable prospective therapeutic target for human cancer immunotherapy (e.g., GBM, KIRC, LGG, and LIHC).